2001
DOI: 10.1002/1097-0029(20010101)52:1<89::aid-jemt11>3.3.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology of choroid plexus: Special reference to metal‐induced neurotoxicities

Abstract: The chemical stability in the brain underlies normal human thinking, learning, and behavior. Compelling evidence demonstrates a definite capacity of the choroid plexus in sequestering toxic heavy metal and metalloid ions. As the integrity of blood-brain and blood-CSF barriers, both structurally and functionally, is essential to brain chemical stability, the role of the choroid plexus in metal-induced neurotoxicities has become an important, yet under-investigated research area in neurotoxicology. Metals acting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 101 publications
(66 reference statements)
3
34
0
Order By: Relevance
“…Chronic exposure to manganese in rats resulted in a decrease in plasma iron, but a marked increase in CSF concentrations of iron (48). The brain regulates iron balance through three, well-coordinated systems: the influx of iron by transferrin receptor (TfR)-mediated transport at brain barriers, the storage of iron dependent on availability of ferritin in neurons and neuroglia, and the efflux of iron by bulk CSF flow to the blood circulation (49)(50)(51). The expression of TfR is posttranslationally regulated by a 4Fe-4S containing protein known as cytoplasmic aconitase (ACO1) or iron regulatory protein I (IRP-I).…”
Section: Altered Brain Barriers In Parkinsonism: Manganesementioning
confidence: 99%
See 1 more Smart Citation
“…Chronic exposure to manganese in rats resulted in a decrease in plasma iron, but a marked increase in CSF concentrations of iron (48). The brain regulates iron balance through three, well-coordinated systems: the influx of iron by transferrin receptor (TfR)-mediated transport at brain barriers, the storage of iron dependent on availability of ferritin in neurons and neuroglia, and the efflux of iron by bulk CSF flow to the blood circulation (49)(50)(51). The expression of TfR is posttranslationally regulated by a 4Fe-4S containing protein known as cytoplasmic aconitase (ACO1) or iron regulatory protein I (IRP-I).…”
Section: Altered Brain Barriers In Parkinsonism: Manganesementioning
confidence: 99%
“…Lead accumulates in and targets both choroid plexus and hippocampus (51,(66)(67)(68) and this phenomenon may relate to the intimate anatomic contact of both tissues. Perhaps closer anatomical location renders the hippocampus more susceptible to lead diffused from the choroid plexus.…”
Section: Concept Of Blood-brain Regional Barriersmentioning
confidence: 99%
“…In the brain, gold accumulated in astrocytes and neurons. The blood-brain barrier (BBB) is scarcely permeable to gold, however, gold may be sequestered by the choroid plexus as an essential Central Nervous System (CNS) defense mechanism [16]. The neurotoxicity of gold has received little attention in modern medical literature and conclusions are still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…11,14,28 Until now, the involvement of the blood-CSF barrier in transfer of Hg compounds remains largely unexplored to our knowledge. In the present study we applied a well characterized cell culture model of the blood-CSF barrier derived from PCPECs 19 to investigate effects on and transfer across this important barrier in both directions (influx and efflux) after exposure to organic (MeHgCl and thiomersal) and inorganic (HgCl 2 ) mercury compounds for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…So far the transfer of the respective organic mercury compounds across this physiological barrier has not been characterized, albeit some evidence exists that cells of the choroid plexus accumulate mercury. 14 A Hg accumulation in the choroid plexus tissue of MeHg treated rats as well as a mercury deposition in epithelial choroid plexus cells of a Minamata disease patient 26 years after exposure is described. 15,16 Additionally, Nakamura et al concluded, that in rats a repeated oral administration of MeHgCl (10 mg kg À1 b.w.)…”
Section: Introductionmentioning
confidence: 96%